2005
DOI: 10.1103/physreve.72.052903
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transitions in small world networks: Approach to equilibrium limit

Abstract: We study the transition to phase synchronization in a model for the spread of infection defined in a small world network. It was shown [Phys. Rev. Lett. 86, 2909 (2001)] that the transition occurs at a finite degree of disorder p, unlike equilibrium models where systems behave as random networks even at infinitesimal p in the infinite-size limit. We examine this system under variation of a parameter determining the driving rate and show that the transition point decreases as we drive the system more slowly. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 16 publications
1
27
2
Order By: Relevance
“…From these observations, we suggested that these patterns were determined by competition be- * E-mail: garuda@skku.edu tween the typical life cycle of the disease and the time taken by it to go around the world [22]. This proposition is consistent with the remark by Gade and Sinha [21] that the time scales are quite important. Roxin et al [9] in this spirit even though they treated a neuron system.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…From these observations, we suggested that these patterns were determined by competition be- * E-mail: garuda@skku.edu tween the typical life cycle of the disease and the time taken by it to go around the world [22]. This proposition is consistent with the remark by Gade and Sinha [21] that the time scales are quite important. Roxin et al [9] in this spirit even though they treated a neuron system.…”
Section: Introductionsupporting
confidence: 81%
“…The interacting element can be a nonlinear oscillator [5][6][7], an excitable neuron [8][9][10][11], a biological species [12,13], a sand pile [14][15][16], an epidemic disease [17][18][19][20][21][22][23], or even a game participant [24][25][26]. These approaches help one to analyze various aspects of this world, including biology, sociology, politics, and economy, as well as the physics itself [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In the modeling of many interacting particles on the networks, the effect of the networks structure on the properties of dynamical systems defined on such networks has been attracted a lot of attention recently, and researchers from fields ranging from neurodynamics and ecology to social sciences have been extensively working in this area [1,2,3,4,5,6,7,8]. In small world networks [6], one starts with a ring of N nodes, in which each node connected to its k nearest neighbors on either side.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we added sources of infection in the model, i.e. a limited number of infective individuals remain in this state all the time [8].…”
Section: Numerical Calculationsmentioning
confidence: 99%